Association between insulin resistance and diabetic kidney disease among adults with type 1 diabetes - Tao Liu; Yan Zhou; Jie Zhou; Jian-fang Fu; Li Wang; Ying Xing; Li-jun Ren; Qiu-he Ji (Linchuang shenzangbing zazhi)
Objective To explore the association between insulin resistance （IR） and diabetic kidney disease （DKD） among adults with type 1 diabetes mellitus （T1DM） and compare multiple surrogate parameters of IR for their associations with DKD in this population. Methods For this cross-sectional study， 556 adults with classic T1DM admitted into Xijing Hospital between October 2008 and June 2021 were enrolled. Demographic， anthropometric and laboratory data were collected. IR-related parameters of estimated glucose disposal rate （eGDR）， metabolic score for insulin resistance （METS-IR） and triglyceride-glucose index （TyG） were calculated. They were categorized into two groups of DKD and non-DKD. The relationship between IR and DKD was explored by binary Logistic regression and restricted cubic spline （RCS） models. Receiver operating characteristic （ROC） curves were plotted for comparing the discriminatory performance of all parameters. Results Median age was 31.0（24.8，44.0） year and median disease duration 6.0（2.0，12.0） year. The prevalence of DKD was 20.14%. Lower eGDR was associated with a high prevalence of DKD. In multivariable analysis， as compared to quartile 1 （Q1）， odds ratios （OR， 95%CI） of DKD for participants in eGDR calculated with body mass index （eGDRBMI） Q2-Q4 were 1.08（0.40-2.92）， 0.13（0.03-0.45） and 0.26（0.07-0.83）， respectively. The corresponding risk in eGDR calculated with waist-to-hip ratio （eGDRWHR） Q2-Q4 was 0.68（0.20-2.23）， 0.51（0.15-1.66） and 0.16（0.03-0.72）， respectively. TyG， eGDR calculated with waist circumference （eGDRWC）， METS-IR， body mass index， waist-to-height ratio and waist-to-hip ratio were not significantly associated with the prevalence of DKD. Subgroup analyses indicated that the association between eGDRBMI and DKD was consistent with overall population in six subgroups of females， age 28-＜40 years and ≥40 years， disease duration ≥5 years， non-smokers and individuals with a family history of diabetes. RCS hinted at a linear and negative correlation between eGDRBMI， eGDRWHR and the prevalence of DKD. ROC analyses indicated that the cutoff values for identifying DKD were 8.23 mg·kg−1·min−1， 7.22 mg·kg−1·min−1 and 7.92 mg·kg−1·min−1 for eGDRBMI， eGDRWHR and eGDRWC， respectively. After adding into a basic model， all three eGDRs demonstrated incremental discriminatory performance. Conclusion IR， reflected by a declining eGDR， is associated with the prevalence of DKD among adults with classic T1DM. And eGDR has demonstrated some potential in identifying DKD in adult classic T1DM and its clinical implication should be validated by more studies.